2021
DOI: 10.1063/5.0028079
|View full text |Cite
|
Sign up to set email alerts
|

Emerging van der Waals ferroelectrics: Unique properties and novel devices

Abstract: The past few decades have witnessed extensive and intensive studies on ferroelectric materials with switchable electric polarization due to their broad device applications. Emerging van der Waals (vdW) layered ferroelectrics ingeniously assemble strong covalent-bonded polar or non-polar monolayers through weak vdW forces. These atom arrangements contrast with the stacking of conventional oxide ferroelectrics, enabling unprecedented ferroelectric physics in terms of polarization origin, polar stabilization, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 113 publications
(119 reference statements)
0
28
0
1
Order By: Relevance
“…thus attracting increasing attention in recent years. [1][2][3][4][5][6] The spontaneous polarization of the ferroelectrics could serve as an electrostatic knob to actively tune the carrier concentrations of the 2D semiconductors and consequently, their electronic transport, luminescent, and optoelectronic properties. [7][8][9][10][11][12][13] As a predominant interface effect, the electrostatic coupling pivots on the quality of the vdW interface between the ferroelectric and the semiconductor.…”
mentioning
confidence: 99%
“…thus attracting increasing attention in recent years. [1][2][3][4][5][6] The spontaneous polarization of the ferroelectrics could serve as an electrostatic knob to actively tune the carrier concentrations of the 2D semiconductors and consequently, their electronic transport, luminescent, and optoelectronic properties. [7][8][9][10][11][12][13] As a predominant interface effect, the electrostatic coupling pivots on the quality of the vdW interface between the ferroelectric and the semiconductor.…”
mentioning
confidence: 99%
“…Similarly, the Raman peak of 3L WSe2 at 20 cm -1 , corresponding to interlayer in-plane shear mode, is observed at 16 cm -1 in 2L and absent in monolayer. 𝐴 𝑔 1 and 𝐴 1𝑔 2 are the first and second-order out-of-plane vibrations between chalcogen atoms, and 𝐸 2𝑔 1 is the first-order in-plane vibration between the transition metal and chalcogen atoms. Since 𝐴 𝑔 1 mode is independent of the incident power, we focus on the 𝐸 2𝑔 1 mode to investigate the photostriction effect.…”
Section: Resultsmentioning
confidence: 99%
“…[61] Finally, the coexistence of OOP and IP polarizations was revealed in the bilayer and monolayer (~1.2 nm) form of hexagonal (2H) α-In 2 Se 3 nanoflake using PFM, as reported by Xue et al [62] The layered α-phase In 2 Se 3 possesses two polymorphs (2H and 3R), and both of them exhibit IP and OOP ferroelectricity at room-temperature. [63,64] Furthermore, few reports claimed that β-In 2 Se 3 also exhibits ferroelectric behaviour even though it is structurally centrosymmetric. For example, in 2018, Zheng et al demonstrated room-temperature IP ferroelectricity in 45 nm thick β-In 2 Se 3 .…”
Section: In 2 Se 3 -An Emerging 2d Ferroelectric Materialsmentioning
confidence: 99%